Vehicle Plate Number Recognition Algorithm for Vehicle Finder System - Liew, Xin Yi; Jong, Siat Ling (Evolution in Electrical and Electronic Engineering, 2020)
Although the smart parking system is a common solution to overcome the issue of parking in the huge shopping mall. However, it encounters a problem on searching their own vehicle in a huge shopping mall which has several levels of parking lots that can accommodate up to hundreds of vehicles. This is due to a visitor has short term memory or easily forget the location of their vehicle parked and lost in the parking lots. Therefore, the visitor needs to spend a lot of time to search for their vehicle based on their short term memory. To this aim, vehicle finder system is proposed to locate the user’s vehicle at the car park. The aim of this work is to develop a vehicle finder system which is based on the vehicle plate number. Vehicle finder system has been developed by using Node-RED programming tool and OpenALPR software is used for the plate number recognition. Once the vehicle plate number has been captured, the plate number will be processed and updated to the Google Spreadsheet and then transferred to the bubble.io database for user to check their vehicle number by using mobile applications. Therefore, when the user keys in their vehicle plate number, the details of the location area and route map will be shown in mobile applications. Such system is benefits to the users that has short term memory in locating their vehicle at huge shopping mall. Moreover, it helps users on saving their time in searching their vehicle at huge indoor parking lots.